King-Devick test normative reference values for professional male ice hockey players - Vartiainen, M. V.; Holm, A.; Peltonen, K.; Luoto, T. M.; Iverson, G. L.; Hokkanen, L. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The King-Devick (K-D) test, a measure of processing speed, visual tracking, and saccadic eye movements, has shown promise as a supplemental screening test following concussion. However, limited normative data for this test have been published.The K-D test was administered to 185 professional ice hockey players as a preseason baseline test in seasons 2012-2013 and 2013-2014. Their average age was 23.8 years (median = 22.0 years, range = 16-40 years). The average K-D score was 40.0 s (SD = 6.1 s, range = 24.0-65.7 s). K-D test performance showed no association with age, education, or the number of self-reported previous concussions in this sample. The association between trials 1 and 2 of the K-D test was good (ICC = 0.92, Pearson = 0.93). Normative values of the K-D test for professional male ice hockey players are reported. K-D test performance did not vary by age, education, or concussion history in this study.